Tahap Penetapan Penahanan pada Tindak Pidana Pencurian Ringan Menurut Restorative Justice di Wilayah Hukum Kepolisian Sektor Pasar Jambi - A, Elvi Alfian (Wajah Hukum, 2025)
Petty theft is a common social problem and reflects challenges in community security. Although considered a minor crime, this theft, which involves taking goods without violence, has a significant impact on the victim. This study aims to determine the process of determining detention in petty theft crimes in the Jambi Market Police Sector and to explain the restorative justice approach in resolving petty theft crimes in the Jambi Market Police Sector. The research method used is empirical juridical using a legal sociology approach so that the data sources used are primary data sources and secondary data sources with data collection techniques in the form of interviews, observations and documentation so that the data analysis technique is qualitative analysis. The results of this study indicate that the detention stage in petty theft cases in the Jambi Market Police Sector The detention determination stage for petty theft crimes in the Jambi Market Police Sector is in accordance with the Criminal Procedure Law. However, the case of theft of a cellphone by Danu Wijaya is not included in petty theft because the loss value is IDR 4,000,000, exceeding the limit of IDR 2,500,000. This case is categorized as ordinary theft and cannot be resolved through a restorative justice approach because the victim does not want to reconcile and Danu is a recidivist with two previous sentences for similar crimes.